Risk level assessment of typhoon-induced wave fields around a large-scale suspended mussel farm - Li, Yanjiao; Lin, Jun; Zhong, Wei; Wang, Sijian; Li, Long (Frontiers in Marine Science, 2024)
Suspended shellfish aquaculture, utilizing longlines and buoys fixed on the sea surface, is a crucial source of global seafood. However, typhoons, as the most common disasters in coastal regions, can generate massive waves and pose a threat to the safety of suspended aquaculture facilities. Therefore, it is essential to investigate the risk levels associated with suspended aquaculture farms during typhoon waves. The example of a large-scale suspended mussel farm in the East China sea was examined in this study. The wave conditions under extreme wind conditions (25m/s) and different typhoon paths were predicted using the SWAN model and modeled results compared well with the observed wave and wind data. The results indicated that when the center of the east-side typhoon was located at the same latitude as the farm, it will face the highest risk level. However, for the west-side and intermediate sweeping typhoons, the risk level reached highest in the farm, when the typhoon center is lower than the latitude of it. Under the combined effects of wind fetch and topography, the risk level in the southeast farming area of the island is the highest under different wind conditions. The farms to the northwest of the island face a higher risk level during the passage of east-side sweeping typhoons, while the southern farms of the island experience an elevated risk level during the west-side and intermediate sweeping typhoons. It is suggested that farming regions with lower risk levels are more conducive to the cultivation of species with longer culture cycles. Conversely, regions considered at higher risk are more suitable for species with shorter culture cycles. The study affords a reference for the optimization and insurance of suspended aquaculture farms.